Revealing the Origin and History of Lead-White Pigments by Their Photoluminescence Properties - Gonzalez, Victor; Gourier, Didier; Calligaro, Thomas; Toussaint, Kathleen; Wallez, Gilles; Menu, Michel (Analytical chemistry (Washington), 2017)
The lead white pigment, composed of two main mineral phases cerussite PbCO and hydrocerussite 2PbCO ·Pb(OH) , has been used in paintings since the Antiquity. The study of historical sources revealed that a large variety of lead white qualities were proposed, depending on the degree of sophistication of the pigment synthesis. Investigation of photoluminescence of the two constitutive mineral phases gave insight into the origin of the visible emission of these materials and emphasized the influence of structural defects on their photoluminescence properties. These effects were observed by combining emission and excitation spectra in two-dimensional representations. For each excitation wavelength, between 250 and 400 nm (4.9-3.1 eV), luminescence spectra were collected between 400 and 800 nm (3.1-1.5 eV). Two types of emission-excitation bands were identified: an emission excited in the optical bandgap of the compounds (about 5 eV), which depends on the constitutive phase (2.8 eV in cerussite and 2.1 eV in hydrocerussite), and broad emission bands in the same energy range excited below the optical gap, which are sensitive to the synthesis method and the nature of postsynthesis treatments. It is proposed that this sensitivity of photoluminescence properties of lead-white pigments could be used as fingerprints of their origin and history.